(untitled) (Вестник КазНУ. Серия математика, механика, информатика, 2018)
We consider the generalized solutions of the non-homogeneous fluid in a magnetic field. Proved a theorem for a generalized solution of an inhomogeneous liquid in a magnetic field .In this article we examine the method of fictitious areas for the non-liner hyperbolic equations. The estimation of rate of convercence decisions is recaived. In some cases the unimproved estimation of convergence rate of the decision is received